Neurocisticercosis: lesión única cerebral con serología negativa y confirmación post exéresis. Reporte de caso. - Arias Torres, Gerardo Andrés; Morinigo, María Alejandra; Urrutia, Mariano; Baldovi, Juan Manuel (Revista Argentina de Neurocirugía, 2021)
The differential diagnoses of single, ring-enhancing brain lesions are multiple, from a parasitic infection to a primary tumor of the central nervous system, therefore, the management of these lesions can be controversial, and the epidemiological prevalence must be taken into account according the demographic situation of the patient. We present the case of a young adult female who was admitted to the neurosurgery service, debuting sensory focal symptoms associated with headache. Brain CT and MRI revealed a subcortical cyst-like lesion in the left superior postcentral gyrus, with large perilesional edema and peripheral enhancement following contrast administration. Serological test for CNS parasites in serum and CSF were negative. Consequently, we realized a complete removal of the cyst with intraoperative ultrasound to optimize the surgical time and the cortical surgical area. The histopathological examination revealed a degenerating cysticercus. For this reason, a bibliographic research was carried out to identify the sensitivity of serological tests for the diagnostic confirmation of neurocysticercosis and thus avoid invasive neurosurgical interventions.
Keywords: Neurocysticercosis; Central Nervous System Cysticercosis; Brain Cysticercosis; Parasitic Sensitivity Test